The Case for Decentralized Federalism - Hubbard, Ruth, 1942-; Paquet, Gilles (Book collections on Project MUSE., 2010)
"The Case for Decentralized Federalism brings together an array of experts around one key idea: decentralized federalism as the best political arrangement for a diverse nation like Canada, Edited by Ruth Hubbard and Gilles Paquet, this book argues that decentralized federalism can most effectively address Canada's regional differences and cultural diversity by dividing the work of public governing among different levels of government, allowing each to address the needs and aspiration of its citizens." "With contributions from Thomas J Courchene, Ian Peach, Gerard Belanger, Hugh D. Segal, Francois Rocher, Marie-Christine Gilbert, Ruth Hubbard and Gilles Paquet, this book presents various arguments for decentralized federalism that show how a variety of issues nagging Canada today---nation-building, subsidiarity, competition, innovation---might be resolved through decentralized federalism." "For the case against decentralization, look for The Case for Centralized Federalism edited by Gordon DiGiacomo and Maryantonett Flumian, also published by the University of Ottawa Press."--Jacket.